Pemberdayaan Pengolahan Limbah Rumah Tangga Melalui Pelatihan Pembuatan Sabun Dari Minyak Jelantah Pada Warga Desa Brambang Kabupaten Demak - Ali Khasan Al Farishi; Danang Priyadi; Ahmad Husain; Ninda Octaviani; Pramesuari Rajwa; Siti Lathifatul Fajriyah; Sinta Prima Dayanti; Yasmin Latifah; Arizka Suci Nurrohmah; Dina Dwi Woro Sehati; Rizki Nur Indah Sari; Muhammad Arvin Najikh; M. Syifa’uddin; Imanniatul Afitikha; Indah Wulan Sari; Fenny Bintarawati (BADAN PENERBIT STIEPARI PRESS, 2024)
Household waste is the largest contributor to waste in the community. Training on making used cooking oil soap is a method taken for this community service activity. The main objective of this training activity is so that people can utilize used cooking oil waste into items that can be used again. The methods used in this training activity are lectures and small group discussions. Making soap from waste is actually very easy, namely by mixing NaOH, used cooking oil and fragrance. The mixture of ingredients is then stirred for about 15-20 minutes and then left for about two weeks until it completely hardens. Used cooking oil soap can be used as hand washing soap and dish washing soap. Extension activities give a different impression to the people who take part in these activities. Based on participant interviews, the mothers felt happy because they could use used cooking oil waste to make soap. It can be concluded that this soap making training is beneficial for the local community, especially housewive.